The COERSEA Model for Interactive Presentations - Koppi, T.; Pearson, E. (Journal of University Teaching and Learning Practice, 2005)
A commonly accepted theoretical paradigm in theresearch and practice of effective learning and teaching isconstructivist. Researchers and practitioners in the highereducation community attend educational technologyfocused conferences to share their findings, seekfeedback and collaboration, or challenge. Althoughresearchers may espouse constructivist methods in theirlearning designs, this model is not adopted in theirpresentations. Often a more traditional transmissionapproach is used with the presenter inflicting manycontent heavy slides on an increasingly passive audience.The COERSEA model (context, outcomes, engagement,resources, support, evaluation, alignment) comprisesseven principles that can be applied to the design of anypresentation be it a lecture, seminar or conference paper.The model compliments current trends in online learningdesign and represents a constructivist approach topresentations that engages participants in a sharedlearning experience. The model has been successfullyapplied to a number of topics and contexts atconferences, seminars and workshops.